Hypoxic Viable Tissue in Human Chronic Cerebral Ischemia Because of Unilateral Major Cerebral Artery Steno-Occlusive Disease. Issue 5 (May 2015) - Saura, Hiroaki; Ogasawara, Kuniaki; Beppu, Takaaki; Yoshida, Koji; Kobayashi, Masakazu; Yoshida, Kenji; Terasaki, Kazunori; Takai, Yoshihiro; Ogawa, Akira
<x xml:space="preserve">Abstract</x> Background and Purpose— Positron emission tomography (PET) with radiolabeled 2-nitroimidazoles directly detects hypoxic but viable tissue present in an acute ischemic area in the human brain. This study using PET with 1-(2-18F-fluoro-1-[hydroxymethyl]ethoxy) methyl-2-nitroimidazole (18F-FRP170) aimed to determine whether tissue with an abnormally elevated uptake of 18F-FRP170 exists in human chronic cerebral ischemia because of unilateral atherosclerotic major cerebral artery steno-occlusive disease. Methods— 18F-FRP170 PET was performed, and cerebral blood flow and metabolism were assessed using 15O-gas PET in 20 healthy subjects and 52 patients. A region of interest (ROI) was automatically placed in 3 segments of the middle cerebral artery territory in both cerebral hemispheres with a 3-dimensional stereotaxic ROI template using SPM2, and each PET value was determined in each ROI. The ratio of values in the affected versus contralateral hemispheres was calculated for the 18F-FRP170 PET image. Results— A significant correlation was observed between oxygen extraction fraction and 18F-FRP170 ratios (ρ=0.509; P<0.0001) in a total of 156 ROIs in 52 patients. The specificity and positive-predictive value for a combination of an elevated oxygen extraction fraction and a moderately reduced cerebral oxygen metabolism for detection of an abnormally elevated 18F-FRP170 ratio (19 ROIs: 12%) were significantly greater than those for the individual categories (elevated oxygen extraction fraction, moderately reduced cerebral oxygen metabolism, or reduced cerebral blood flow). Conclusions— Tissues with abnormally elevated uptake of 18F-FRP170 exist in human chronic cerebral ischemia characterized by a combination of misery perfusion and moderately reduced oxygen metabolism because of unilateral atherosclerotic major cerebral artery steno-occlusive disease.